2003
DOI: 10.1042/bj20021259
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of heparan sulphate with diverse structures and functions: two alternatively spliced forms of human heparan sulphate 6-O-sulphotransferase-2 having different expression patterns and properties

Abstract: Heparan sulphate 6- O -sulphotransferase (HS6ST) catalyses the transfer of sulphate from adenosine 3'-phosphate, 5'-phosphosulphate to the 6th position of the N -sulphoglucosamine residue in HS. We previously described the occurrence of three isoforms of mouse HS6ST, mHS6ST-1, -2, and -3 [Habuchi, Tanaka, Habuchi, Yoshida, Suzuki, Ban and Kimata (2000) J. Biol. Chem. 275, 2859-2868]. In the present study, we have characterized HS6ST-2 and HS6ST-1 human isologues, including their chromosomal localizations. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 50 publications
2
54
0
1
Order By: Relevance
“…This repeating unit was 39% of that in heparin prepared from HS6ST-2 Ϫ/Ϫ ear and 64% of that in the heparin prepared from WT ear. We previously reported that HS6ST-2 showed a higher preference for IdoUA(2SO 4 )-GlcNSO 3 as the acceptor than HS6ST-1, although the substrate specificity of the three HS6ST isoforms (HS6ST-1, HS6ST-2, and HS6ST-3) overlapped (8,10). The effects of the targeting destruction of HS6ST-1 or HS6ST-2 on heparin structure appear to be consistent with these enzymatic properties.…”
Section: Discussionmentioning
confidence: 69%
“…This repeating unit was 39% of that in heparin prepared from HS6ST-2 Ϫ/Ϫ ear and 64% of that in the heparin prepared from WT ear. We previously reported that HS6ST-2 showed a higher preference for IdoUA(2SO 4 )-GlcNSO 3 as the acceptor than HS6ST-1, although the substrate specificity of the three HS6ST isoforms (HS6ST-1, HS6ST-2, and HS6ST-3) overlapped (8,10). The effects of the targeting destruction of HS6ST-1 or HS6ST-2 on heparin structure appear to be consistent with these enzymatic properties.…”
Section: Discussionmentioning
confidence: 69%
“…We demonstrated previously that in mammals, heparan sulfate 6-O-sulfotransferases exist in three isoforms (HS6ST-1, -2, and -3) and one alternatively spliced form (HS6ST-2S) (30,31). Although the substrate specificities of these isoforms largely overlap, the individual isoforms exhibit a characteristic preference for the uronic acid residue neighboring the N-sulfoglucosamine.…”
Section: Heparan Sulfate (Hs)mentioning
confidence: 99%
“…28) cDNAs. No PCR product was observed using primers for 6-OST3, indicating that the 293 cells express 6-OST1 and 6-OST2S mRNA endogenously, as verified by sequencing of the purified PCR fragments (data not shown).…”
Section: Enzymatic 6-o-sulfation Of 3 H-labeled Octasaccharides-mentioning
confidence: 99%